INOVASI METODE PEMBELAJARAN PAI MELALUI DARING PADA MASA PANDEMI DI SMP NEGERI SIMPANG KOSGORO MUSI RAWAS - SUHARNI SUHARNI (IAIN Bengkulu, 2021)
The purpose of this study is to answer the following research questions: 1) What methods are used by Islamic Religious Education teachers in providing material during the current pandemic at SMP Negeri Simpang Kosgoro, Musi Rawas Regency ?, 2) What are the inhibiting and supporting factors faced in innovation methods by Islamic Religious Education teachers in providing material during the current pandemic at SMP Negeri Simpang Kosgoro, Musi Rawas Regency ?, and 3) What are the student learning outcomes in taking Islamic Religious Education learning during the Covid 19 pandemic at SMP Negeri Simpang Kosgoro, Musi Rawas Regency ? This study uses a qualitative approach using descriptive methods. The results of this study indicate that: 1) The method used by Islamic Religious Education teachers in providing material during the current pandemic at SMP Negeri Simpang Kosgoro, Musi Rawas Regency, is a guided learning method to students. Through guided learning methods can make students excited in learning. 2) Student innovation in participating in Islamic Religious Education learning during the Covid 19 pandemic at the Simpang Kosgoro State Middle School, Musi Rawas Regency, is that students are expected to develop their potential in participating in learning through watshapp (WA). 3) Obstacles and solutions of Islamic Religious Education teachers in motivating students to understand and practice the values of Islamic Religious Education subject matter at SMP Negeri Simpang Kosgoro, Musi Rawas Regency, which is seen from the internal factors that affect the interest in learning Islamic Religious Education at SMP Negeri Simpang Kosgoro, Musi Regency. Rawas is influenced by the talents and abilities of students and external factors that affect the interest in learning Islamic Religious Education at SMP Negeri Simpang Kosgoro, Musi Rawas Regency is influenced by the family, because family is important in the success of learning, facilities and infrastructure also affect interest in learning, fiber environment also influences external factors of interest in learning at school.